Morphemes and vocabulary: A world apart? - Engku Ibrahim, Engku Haliza; Ahmad Zaki, Azimah (2014)
Findings from a few studies suggest that morphological awareness may be useful for vocabulary development. It is also suggested that knowing how to form words is an essential skill needed for language learners to be competent users of the English language. This paper presents the findings of a study which aims to investigate the relationship between morphological awareness and vocabulary knowledge. A quantitative research design based on two sets of tests was employed for the purpose of the study. The two tests were Morphological Awareness Test (MAT) adopted from McBride et al (2005) and Vocabulary Level Test (VLT) adopted from Schmitt et al (2001). The MAT assesses the skills of identifying morphemes, while the VLT provides an estimation of the students’ vocabulary size. A total of 100 Malay ESL pre-university students participated in this study. The findings of the study, based on correlation analysis, indicate no relationship between students’ performance in MAT and VLT. It was found that students’ morphological awareness was not related to their vocabulary knowledge. The findings also revealed that the students had limited morphological awareness and vocabulary knowledge. Relevant recommendations are also included.